Land Suitability Of Mango (Mangifera indica L.) Plants By Utilizing Geographic Information Systems (GIS) - Sandra E. Pakasi; Junivia Virginia Jermias; Diane D. Pioh (Jurnal Agroekoteknologi Terapan, 2023)
The study of land suitability evaluation is very needed in agriculture. This study aims to determine the land suitability class and the distribution map of the land suitability class for Mango plants in East Lembean District by utilizing the Geographic Information System (GIS). This study uses a field survey method. In this study, land units were obtained from the results of overlapping land use maps and slopes, consisting of seven land units. Data collection techniques in the form of documentation, observation and laboratory analysis. The data analysis technique to determine the land suitability class uses the matching technique by matching the parameters and land quality so that the land suitability class for mango plants is obtained. The conclusion of this study is that land suitability for mango plant development in East Lembean District is generally in the land suitability class S1 (very suitable) for the criteria for nutrient retention and rooting media, while the criteria for temperature and available nutrients are included in the land suitability class S2 (quite suitable) and for the hazard level criteria. erosion entered in class S3 (according to marginal). Keywords: land suitability, geographic information systems, Mangivera indica L. Abstrak Kajian evaluasi kesesuaian lahan sangat diperlukan dalam bidang pertanian. Penelitian ini bertujuan untuk mengetahui kelas kesesuaian lahan dan peta persebaran kelas kesesuaian lahan tanaman Mangga di Kabupaten Lembean Timur dengan memanfaatkan Sistem Informasi Geografis (SIG). Penelitian ini menggunakan metode survei lapangan. Pada penelitian ini satuan lahan diperoleh dari hasil tumpang tindih peta penggunaan lahan dan lereng yang terdiri dari tujuh satuan lahan. Teknik pengumpulan data berupa dokumentasi, observasi dan analisis laboratorium. Teknik analisis data untuk menentukan kelas kesesuaian lahan menggunakan teknik pencocokan dengan mencocokkan parameter dan kualitas lahan sehingga diperoleh kelas kesesuaian lahan untuk tanaman mangga. Kesimpulan dari penelitian ini adalah kesesuaian lahan untuk pengembangan tanaman mangga di Kecamatan Lembean Timur secara umum berada pada kelas kesesuaian lahan S1 (sangat sesuai) untuk kriteria retensi hara dan media perakaran, sedangkan kriteria suhu dan hara tersedia termasuk dalam kelas kesesuaian lahan S2 (cukup sesuai) dan untuk kriteria tingkat bahaya. erosi masuk dalam kelas S3 (menurut marjinal). Kata kunci: kesesuaian lahan, sistem informasi geografis, Mangivera indica L.